(untitled) (Medico Legal Update, 2020)
Burn injuries are a public health problem in developing countries like India specially in females. Our objective of the present study is to know the pattern of deaths due to burns, socio etiological factors involved and to suggest preventive measures. A study based on autopsies conducted in R.N.T. Medical College, Udaipur (from 1st March 2018 to 30th September 2018) where total 780 Medico-legal autopsies were conducted during this period , out of those 86 were due to burn. 45 victims were male and 41 were female. Maximum 46 of the cases were in the 21-40 years of the age group in both genders. Most of the cases were found to be from rural area (80.23%). The most common manner of burn was accidental (74.41%) followed by suicidal burns (22.09%). Majority of victims died as a result of flame burn (74.41%) and death due to flame, major cases were females (62.5%). Majority of victims (41.86%) died with more than 80% burns and (52.32%) victims could not survive for more than 24 hours. The cause of death in (52.32%) cases was shock followed by septicemia in (32.5%).